Vocational education and training in Germany : short description - Hippach-Schneider, Ute [Verfasser]; Krause, Martina [Verfasser]; Woll, Christian [Verfasser] (Office for Official Publications of the European Communities, 2007)
This overview of vocational education and training in Germany has been produced to mark Germany's Presidency of the Council of the EU. It forms part of the series of short descriptions regularly published by Cedefop on national VET systems. Germany is one of the European countries in which learning on the job is a traditional component of the education system. All vocational training is aimed at imparting comprehensive professional competence in the occupation. Vocational training in Germany is guided not only by the requirements of the labour market, but also by the need for individuals to acquire skills, knowledge and competences that enable them successfully to prove themselves on the labour market. Continuing vocational training is playing an increasingly important role in the context of lifelong learning in order to continually enhance the professional capabilities of the individual. The State has only minor regulatory and organisational responsibilities. (BIBB2)
Keywords: Berufsbildungssystem; Duales System; Bildungspolitik; Berufsbildendes Schulwesen; Berufsausbildung; Bildungspersonal; Kompetenzentwicklung; Ausbildungsordnung; Berufliche Weiterbildung; Berufsberatung; Berufsorientierung; Bildungsfinanzierung; Bundesrepublik Deutschland